PENTINGNYA PENDIDIKAN DAN KETERAMPILAN DALAM MENINGKATKAN ETOS KERJA PEGAWAI DI KANTOR KECAMATAN ULUGAWO KABUPATEN NIAS - Gori, Saforius; Telaumbanua, Eliagus; Harefa, Peringatan; Waruwu, Sukaaro (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Until now, an employee's level of education at the Ulugawo District Office in Nias Regency has been ignored and has not fully supported the improvement of employee performance, as there is a lack of employee discretion in carrying out their duties, decision-making authority is still limited, and there is a lack of feedback. The research aimed to examine the importance of education and skills in improving employee ethics at the Ulugawo District Office in Nias Regency. The qualitative research methodology was applied. The study's findings demonstrate that having an education and qualifying abilities might assist enhance the work ethic of employees at the Ulugawo Sub-District Office. Higher education usually provides an improved understanding of employees' tasks and obligations. Qualified skills may also help employees do their tasks more efficiently and successfully. Keywords: Work Ethic; Education; Skills